2018
DOI: 10.1186/s12938-018-0479-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of plate systems for proximal humerus fractures: a systematic literature review

Abstract: BackgroundProximal humerus fractures are the third most common in the human body but their management remains controversial. Open reduction and internal fixation with plates is one of the leading modes of operative treatment for these fractures. The development of technologies and techniques for these plates, during the recent decades, promise a bright future for their clinical use. A comprehensive review of in vitro biomechanical studies is needed for the comparison of plates’ mechanical performance and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 127 publications
(399 reference statements)
0
32
0
2
Order By: Relevance
“…The various plate systems designed for the proximal humerus have been compared in numerous biomechanical studies which showed the superiority of locking implants over conventional implants [24]. In a study by Hessmann et al, using a 3-part fracture model with 8 formalin-fixed human humerus pairs, DP with a laterally placed and a second anteriorly placed third-tubular plate was compared to the locking PHILOS plate [25].…”
Section: Proximal Humerusmentioning
confidence: 99%
“…The various plate systems designed for the proximal humerus have been compared in numerous biomechanical studies which showed the superiority of locking implants over conventional implants [24]. In a study by Hessmann et al, using a 3-part fracture model with 8 formalin-fixed human humerus pairs, DP with a laterally placed and a second anteriorly placed third-tubular plate was compared to the locking PHILOS plate [25].…”
Section: Proximal Humerusmentioning
confidence: 99%
“…Ein Großteil der Humeruskopffrakturen findet im höheren Patientenalter statt und ist mit geringerer Knochendichte verbunden; winkelstabile Plattenosteosynthesen mit vorgeformten Implantaten, wie beispielsweise das von der AO zugelassene Proximal Humeral Internal Locking System (PHILOS, Firma Synthes), haben hier in biomechanischen Testungen eine deutliche Überlegenheit nicht winkelstabilen Implantaten gegenüber gezeigt. Je nach Frakturmorphologie und Knochenqualität ist zusätzlich eine Augmentation der Schrauben mit Zement möglich oder die zusätzliche Implantation eines Allografts zur Wiederherstellung einer medialen kortikalen Abstützung [15] (▶ Abb. 5).…”
Section: Anwendungsbeispiele Humerusunclassified
“…Numerous in vitro biomechanical studies have demonstrated enhanced primary stability of proximal humerus plating with cement-augmented screws. 9 , 12 However, the clinical findings have been controversial regarding the benefit of bone cement augmentation with the proximal humerus internal locking system (PHILOS; DePuy Synthes, Zuchwil, Switzerland). 13 - 15 These variable results may be related to heterogenicity of augmentation techniques and the screw configurations used.…”
Section: Introductionmentioning
confidence: 99%